Materi Dan Strategi Guru Bk Dalam Membina Adab Siswa - Safitri, Azsyurah; Tambusai, Khairuddin (Universitas Pakuan, 2025)
MATERIALS AND STRATEGIES OF BK TEACHERS IN FOSTERING STUDENT MANNERSThis qualitative research aims to obtain information regarding the materials and strategies of guidance and counseling teachers in fostering student morality. The data sources were guidance and counseling teachers and students. Data collected through observation, interviews, and documents were analyzed using qualitative analysis techniques. The results of this study indicate that the materials provided by guidance and counseling teachers in fostering student morality include morality, social behavior, and other topics integrated with Islamic law. These materials are implemented in accordance with the guidance and counseling perspective, although not optimally. Guidance and counseling teachers, in implementing guidance and counseling services for students, have not collaborated well with subject teachers. This is due to their respective busy schedules and misperceptions regarding the functions of guidance and counseling. In implementing guidance and counseling services, the strategy employed by guidance and counseling teachers is to provide materials with an Islamic sharia approach, which has a positive influence and inspires students, enabling them to gain direction and purpose from the material, leading to greater civility and closerness to God. Furthermore, the implementation of guidance and counseling services in fostering student morality has received a positive response from students, although in practice, students have not utilized the counseling services as intended. Guidance and counseling teachers also establish relationships with parents through home visits.